TaTypA, a Ribosome-Binding GTPase Protein, Positively Regulates Wheat Resistance to the Stripe Rust Fungus - Liu, Peng; Myo, Thwin; Ma, Wei; Lan, Dingyun; Qi, Tuo; Guo, Jia; Song, Ping; Guo, Jun; Kang, Zhensheng (Frontiers in Plant Science, 2016)
Tyrosine phosphorylation protein A (TypA/BipA) belongs to the ribosome-binding GTPase superfamily. In many bacterial species, TypA acts as a global stress and virulence regulator and also mediates resistance to the antimicrobial peptide bactericidal permeability-increasing protein (BPI). However, the function of TypA in plants under biotic stresses is not known. In this study, we isolated and functionally characterized a stress-responsive TypA gene (TaTypA) from wheat, with three copies located on chromosomes 6A, 6B and 6D, respectively. Transient expression assays indicated chloroplast localization of TaTypA. The transcript levels of TaTypA were up-regulated in response to treatment with methyl viologen, which induces ROS in chloroplasts through photoreaction, cold stress and infection by an avirulent strain of the stripe rust pathogen. Knock down of the expression of TaTypA through virus-induced gene silencing (VIGS) decreased the resistance of wheat to stripe rust accompanied by weakened reactive oxygen species (ROS) accumulation and hypersensitive response (HR), an increase in TaCAT and TaSOD expression, and an increase in pathogen hyphal growth and branching. Our findings suggest that TaTypA contributes to resistance in an ROS-dependent manner.